The Role of Pesantren Culture in The Formation of Student Character Education at Al-Anam Islamic Boarding School Cianjur - Hariyanto, Teguh; Tamlekha, Tamlekha; Ropi Fahmi, Dede; Assalaam, Sunan Hanif Ihsan; Basri, Hasan (Jurnal Ilmiah Teunuleh, 2026)
The culture of the pesantren is a living value system and plays an important role in the formation of the character of the students. This study aims to analyze the role of pesantren culture in shaping the character education of students at the Al-Anam Cianjur Islamic Boarding School. The research uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, participatory observations, and documentation. The research informants included kyai, ustadz, pesantren administrators, and students. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The validity of the data is maintained through triangulation of sources and techniques. The results of the study show that the pesantren culture at Al-Anam Islamic Boarding School, which includes daily discipline, ta'dzim attitude towards teachers, mutual cooperation, simplicity, independence, and the tradition of recitation of the yellow book, plays a significant role in shaping the character of students. The character values formed include sincerity, responsibility, discipline, humility, independence, tolerance, and honesty. The culture of pesantren has proven to be an effective character education system because these values are internalized through example, habituation, and religious boarding life. This study recommends strengthening the culture of pesantren as a model of Islamic character education that is relevant to the challenges of modern education.